GAMBARAN TEKANAN DARAH SISI TANGAN YANG NORMAL DENGAN SISI TANGAN YANG PARESE PADA PASIEN STROKE - Zuliani Zuliani (Jurnal EDUNursing, 2018)
ABSTRACT Blood pressure consists of pressure systole and diastole. Stroke is a brain disorder caused by a pathological process in the blood vessel system of the brain. Stroke can cause various neurological deficits. The purpose of this study was to determine systolic and diastolic blood pressure in the normal hand side and hand side that was paralyzed in stroke patients. This study is quantitative with descriptive research design. The population was stroke patients who had parese in Mojowarno Hospital consisting of 45 respondents selected using simple random sampling and instruments using questionnaires. The results of the study obtained gender mostly male 30 people (66%) and aged 61-70 years as many as 25 people (56%) and almost half of the respondents were elementary school level as many as 22 people (49%) and most of the work was private as much 27 people (61%). Whereas the measurement of respondent's blood pressure with mean hand systole with a value of 145 and mean diastole with a value of 92, while the mean extremity of systole with a value of 147 and mean diastole with a value of 94. There is no difference in blood pressure measurement results. between the sides of the normal hand with the parese side of the hand. Both the normal and hand side of the hand that parese has the same opportunity or possibility to produce higher or lower results. This result is also used to prove that the measurement of blood pressure on one side of the hand cannot represent measurements on both hands because vascular abnormalities can occur anywhere both right and left hand, so that examination of just one side of the hand can cause poor interpretation of results right. Keywords: Measuring, Blood Pressure, Stroke.